Caring for Different Economic Conditions to Maintain the Social Integration of Multi-Ethnic Farmers - Muhammad Arsyad; La Tarifu; Harnina Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study examines the concern for differences in economic conditions in maintaining the social integration of multi-ethnic farmers. Data collection was carried out by interviewing informants. The selection of informants is carried out using the snowball method, that is, finding key informants who have knowledge of the differences in social conditions, the process of social integration of farmers, then key informants indicate other informants. The results showed that differences in economic conditions were based on wealth/area of rice field ownership, ownership status, labor, production and income, marketing, savings and investment, consumption patterns, and capital. This leads to inequalities and knowledge gaps, differences in the ability to cope with the problems of the production process. The solution of caring for each other can maintain the social integration of multi-ethnic farmers. Social integration of society is characterized by mutual care, order, interdependence, uniformity of thinking, the importance of social order. Strategies of maintaining social integration through concern for different economic conditions, training individuals to accept each other, adjust habits, open up, respect each other and recognize each other. The contribution of the results of this study is beneficial for multi-ethnic communities with different socioeconomic conditions in living a sustainable life together